Pesantren as a Halal Center Institution Towards Religious Tourism Development - Purnama, Tata S.; Zirmansyah, Zirmansyah; Fitriyana, Iyan (Indonesian Journal of Halal Research, 2021)
The pesantren institutions have never lost interest from the young generation. An old pesantren continues the process, and new pesantren keep appearing. The education system and the institutions for pesantren are growing rapidly, as supported by facilities, infrastructure, and curriculum. They are adapted constanly according to the times. The halal center discourse is developing in the global world. It has made the continue of pesantren to offer applicative ideas. Then the institutions can become the promising center for religious tourism. This study used qualitative literature study and interviews to collect data that related to religious tourism in pesantren. It can be concluded that there are five potentials for developing religious tourism and halal centers in pesantren; such as the intrinsic value of the pesantren, the pattern of life, the environment and the surrounding community, the sacredness, and the spiritual atmosphere; and pesantren religious tourism aspect.